INVESTIGATION ON DISSOLUTION PATTERN AND MATHEMATICAL MODELING OF DRUG RELEASE OF QUERCETIN BY COMPLEXATION WITH CYCLODEXTRIN NANOSPONGES - SOBITHARANI P; ANANDAM S; MOHAN VARMA M; VIJAYA RATNA J; SHAILAJA P (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main objective of this study was to investigate the release pattern of a poorly water-soluble drug quercetin (QU) by fabricating its cyclodextrin nanosponges. Methods: Characterization of the original QU powder and QU-loaded nanosponges was carried out by the Fourier-transformed infrared (FTIR) spectroscopy, transmission electron microscopy (TEM), and dissolution tester. The drug release pattern was subjected to various kinetic models. Results: FTIR studies confirmed the formation of inclusion complex of drug. The particle size analysis revealed that the average particle size measured by laser light scattering method is around 400–420 nm with low polydispersity index. The particle size distribution is unimodal and having a narrow range. A sufficiently high zeta potential indicates that the complexes would be stable and the tendency to agglomerate would be miniscule. TEM image revealed the porous nature of nanosponges. The dissolution of the QU nanosponges was significantly higher compared with the pure drug. Conclusion: From the kinetic study, it is apparent that the regression coefficient value closer to unity in case of Korsmeyer-Peppas model indicates that the drug release exponentially to the elapsed time. n value obtained from the Korsmeyer-Peppas plots, i.e., 0.9911 indicating non-Fickian (anomalous) transport ; thus, it projected that delivered its active ingredient by coupled diffusion and erosion.